Investigation of mould design methodology with advanced CAD tools for small and medium enterprises - Luo, Hongjun. (2008)
Develops an associative approach in plastic injection mold design process for most of the local plastic injection mold manufacturers, using native modeling features of a current advanced CAD tool, to investigate a methodology that can achieve the associative relationships between mold geometric entities and the original molding part.